Analisis desain stamping die menggunakan FTI forming suite - Nanang Ali Sutisna; Vicky Gufron Afandi (Jurnal Teknik Mesin Indonesia, 2023)
This study was conducted on stamping die design for one of the car body parts using the FTI Forming Suite software. In general, the design process of existing stamping dies in the observed companies involves seven to ten trials before obtaining an acceptable die, which consequently increases the cost of the die. By using the software, it is expected that the number of trials will be reduced because the design is analyzed first to identify unwanted defects in the stamping process, such as wrinkles, splits, and springbacks. The study begins by comparing the stamped parts with the design. Using a 3D scanner, the geometry of the parts is obtained and compared to a original 3D CAD model to check for deviations of the parts from the original design. Comparison between the stamped parts and the original design shows discrepancies. This is most likely because the design has been modified to prevent stamping defects. Furthermore, the original design is simulated by applying a blank holder force of 109.7 kN. The first simulation on the original design showed that the thickness strain was -14.4% and had a strong wrinkling tendency, therefore the modified design was then simulated again on this modified part design. Modifications mainly focused on the essential corner radius, as well as on the blank holder force to 129.2 kN to prevent wrinkling and reduce springback. The second simulation produces good formability as shown by the forming limit diagram (FLD), safety zone, and better springback, even though the minimum thickness strain increases to -19.2%. Thus, by using simulation software, the correct die geometry can be obtained prior to die making to avoid unnecessary die modification costs during the trial run. In addition, the number of trials can be minimized so that the lead time for stamping dies production is shortened.